Koordinasi Dinas Perhubungan dan Kepolisian dalam Meningkatkan Ketertiban Berlalu Lintas di Kabupaten Malang - Sofwatul Alima; R Muhammad Mahrus Alie (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Indonesia is a country with a large number of land transportation users and it is necessary to organize strategies so that it runs well in order to maintain safe and secure traffic. It is hoped that the coordination carried out by the transportation service and the police will have a big impact on traffic order in Malang Regency. The aim of this research is to find out how traffic order is coordinated in Malang Regency, the method used is a case study based on interviews. The results of this research show that the communication process is direct when transportation service officers are in the field, the communication process uses Handy talkie technology, communication from this tool for one direction and one purpose. The competency of participants from the transportation service is more technical, such as checking the condition of vehicle tires, lights and wheel position, understanding vehicle routes in the district, while from the police, it is understanding legal regulations and procedures for implementing enforcement. According to the agreement and commitment, the Transportation Service has limited authority and can only carry out technical matters regarding the condition of vehicles, while the authority of the Police is to take action, therefore there is a need for coordination between the two. Determination of an agreement regarding coordination when there is an activity that requires a number of parties, a formal letter will be written based on the applicable regulations. Coordination incentives show that the implementation of tasks has been coordinated. If a violation occurs, there will be no sanctions but what has been agreed is that responsibility will return to the respective agencies. Due to feedback, the communication process is sometimes long, so the time needed to carry out traffic operations also increases.